The Application of Kufr in the Qurʾān (A Case Study of Sūrah al-Baqarah) - Mohammad Ebrahim Roshanzamir; Mostafa Mahdavi Arjmand (آموزه‌های قرآنی)
A precise understanding of religious terminology necessitates not only an awareness of its lexical and terminological meanings but also a thorough examination of its Qurʾānic and ḥadīth-based applications. Failure to account for this dimension may lead to misinterpretations of scriptural texts. This study, employing a descriptive-analytical methodology, investigates the application of the term kufr (Arabic: کفر) in the Qurʾān with reference to a specific juridical definition, namely "the absence of Islam". Given the extensive occurrence of kufr in the Qurʾān, this research confines its scope to Sūrah al-Baqarah. The findings indicate that the usage of kufr and its derivatives in Sūrah al-Baqarah does not correspond unequivocally to its theological and juridical definition. The Ahl-al-Kitāb (People of the Book), despite their claim to faith, are designated as kuffār (Arabic: کفار, lit: disbelievers) due to their hostile stance towards their own prophets, divine injunctions, and the Prophet Muḥammad (PBUH). Likewise, the polytheists of Mecca are categorized as kuffār not merely due to their non-Muslim status but owing to their particular attributes and adversarial conduct, despite the completion of divine proof (Arabic: إتمام الحجة, Romanized: itmām al-ḥujjah) against them. Thus, an analysis of the contextual nuances of verses addressing kufr, whether concerning the Ahl-al-Kitāb (Arabic: أهل الکتاب), polytheists, or hypocrites, along with an examination of specific instances referenced in the Qurʾān, demonstrates that the designation kāfir (Arabic: کافر) does not universally apply to every non-Muslim individual per se.